2000
DOI: 10.1086/314068
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Bacillus Calmette-Guérin-Activated Killer Cells

Abstract: Tumor regression induced in cancer patients by local instillation of bacillus Calmette-Guérin (BCG) into the bladder is considered to be mediated by cellular immune and inflammatory reactions. In an attempt to elucidate which of these effects are relevant to tumoricidal activity, an in vitro system was employed in which the immunostimulatory effects of BCG could be studied. This report describes the induction of BCG-activated killer (BAK) cells, which effectively lyse bladder tumor cells. Human peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Furthermore, the level of hIFN-g produced by rBCG-induced PBMCs was significantly higher than that in the other 2 groups. Previous studies have demonstrated that IFN-g, TNF-a, and IL-12 are antiproliferative to cancer cells, as well as induce apoptosis (Thanhäuser et al, 1995;Brandau et al, 2000a). In addition, Luo et al (2001) showed that the restructuring of hIFNa-2b-rBCG effectively induced generation of hIFN-g, hTNF-a, and hIL-12, which was clearly higher than that in wild-type BCG and wild-type BCG plus IFN.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the level of hIFN-g produced by rBCG-induced PBMCs was significantly higher than that in the other 2 groups. Previous studies have demonstrated that IFN-g, TNF-a, and IL-12 are antiproliferative to cancer cells, as well as induce apoptosis (Thanhäuser et al, 1995;Brandau et al, 2000a). In addition, Luo et al (2001) showed that the restructuring of hIFNa-2b-rBCG effectively induced generation of hIFN-g, hTNF-a, and hIL-12, which was clearly higher than that in wild-type BCG and wild-type BCG plus IFN.…”
Section: Discussionmentioning
confidence: 91%
“…Both lipoglycans and AMs induced profound anti-tumor cytotoxicity in the range of 40 to 60% of that obtained by M. bovis BCG. BCG has been described as inducing strong natural killer cell-mediated tumor cell lysis in this system and serving as a positive control (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These effector cell types are crucial for BCG immunotherapy of bladder cancer, as depletion of these cell types failed to develop effective anti-bladder cancer responses in vivo and kill bladder cancer cells in vitro (Ratliff et al, 1993;Brandau et al, 2001). It has been shown that stimulation of human peripheral blood mononuclear cells (PBMC) by viable BCG in vitro leads to the generation of a specialized cell population called BCGactivated killer (BAK) cells (Böhle et al, 1993;a Brandau et al, 2000). BAK cells are a CD3 -CD8 + CD56 + cell population whose cytotoxicity is MHC non-restricted ( a,b Brandau et al, 2000).…”
Section: Mechanism Of Bcg Actionmentioning
confidence: 99%
“…It has been shown that stimulation of human peripheral blood mononuclear cells (PBMC) by viable BCG in vitro leads to the generation of a specialized cell population called BCGactivated killer (BAK) cells (Böhle et al, 1993;a Brandau et al, 2000). BAK cells are a CD3 -CD8 + CD56 + cell population whose cytotoxicity is MHC non-restricted ( a,b Brandau et al, 2000). BAK cells kill bladder cancer cells through the perforin-mediated lysis pathway and are effective on lysing NK cell-resistant bladder cancer cells (Böhle et al, 1993; Brandau et al, 2000).…”
Section: Mechanism Of Bcg Actionmentioning
confidence: 99%
See 1 more Smart Citation